A novel geometric-based bistatic range grouping algorithm for multi-target localization in distributed MIMO radar systems - Kang, Seyoung; Shin, Hyuksoo; Chung, Wonzoo (Expert systems with applications, 2024)
In this paper, a novel bistatic range grouping algorithm is proposed in order to localize multiple targets in distributed multiple-input multiple-output (MIMO) radar systems. In a distributed MIMO radar, target localization is performed based on bistatic ranges, the distances between antennas through a target, without directional information, and grouping bistatic ranges with respect to the target is a crucial step to estimate multiple targets efficiently. In contrast to the existing grouping schemes that use tentative target estimation or complicated joint bistatic range grouping and target estimation, the proposed algorithm uses only the geometric property of bistatic ranges, resulting in computationally efficient and robust grouping algorithm without noise enhancement, especially for realistic noisy environments where other existing grouping algorithms often fail. The performance of the proposed scheme is confirmed by evaluating the probability of miss detection and the probability of false alarm through numerical simulations for various environments including indirect paths and blocked paths. The root mean square error performance of the multi-target localization using the proposed bistatic grouping algorithm is also presented for realistic noisy environments. •A novel grouping criterion is proposed to group the bistatic ranges.•A sequential approach reduces the computational complexity of the proposed algorithm.•The proposed algorithm achieves performance improvement in non- ideal environments.